Pedestrianization and walkability in a fast developing unesco world Heritage City - Zainol, R.; Wang, C.; Ali, A.S.; Ahmad, F.; Aripin, A.W.M.; Salleh, H. (Open House International Association, 2016)
A walkability friendly environment is crucial in historical towns and cities built with minimal number of motor vehicles. This research aims to assess physical attributes of pedestrianization in Georgetown, Penang, a UNESCO World Heritage Site regarding walkability. A structured interview was conducted among 170 respondents at six different streets to examine citizens' satisfaction on the pedestrian facilities using six walkability features including a) pathway, b) zebra crossing, c) signage, d) personal safety, e) traffic flow and, f) aesthetics & amenities. Relative Importance Index (RII) analysis show that existing pathways do not meet acceptable standards in promoting a walkable environment. Aesthetic and amenities scores the lowest in satisfactory level and zebra crossing scores the highest in unsatisfactory level. The level of walkability in the World Heritage Site in Georgetown, Penang are found inadequate. Provision of physical walking and built heritage features without providing sufficient activities along the streets do not yield high walkability.